Comparison of the Effectiveness of Narrative Therapy and Schema Therapy on Self-Coherence in Middle-Aged Women - Shekouhideh, Masoumeh; Ghazanfari, Ahmad (Mental Health and Lifestyle Journal, 2025)
This study aimed to compare the effectiveness of narrative therapy and schema therapy on self-coherence in middle-aged women in Shahr-e-Kord. The research method was semi-experimental, with a pre-test-post-test design, including a control group. The statistical population consisted of all middle-aged women in Shahr-e-Kord. After considering the inclusion and exclusion criteria, 60 participants were selected and randomly assigned into three groups of 20 participants each. All three groups completed the self-coherence questionnaire. Michael White’s (1995) narrative therapy protocol and Young et al.’s (2003) schema therapy protocol were used for the interventions. The results indicated that both narrative therapy and schema therapy were effective in improving self-coherence (31.2%). However, narrative therapy had a greater effect on the experiential self-awareness component, and its effectiveness on courage and moderation was significantly higher than that of schema therapy. Therefore, both narrative therapy and schema therapy can be utilized to enhance self-coherence.